HUBUNGAN ANTARA BRAND CREDIBILITY, WORD OF MOUTH, DAN ELECTRONIC WORD OF MOUTH: PERAN MEDIASI BRAND-SELF CONNECTION DAN BRAND-SOCIAL CONNECTION - Fathurrazi Ammana Billa; Evo Sampetua Hariandja; Ray Arvin Febrianto; Rini Yovita Moktar (Universitas Multimedia Nusantara, 2020)
This study was conducted to analyze the relationship between Brand Credibility, Word of Mouth, and Electronic Word of Mouth mediated by Brand-Self Connection and Brand-Social Connection to the Netflix brand in the Greater Jakarta area and generation Z. This study uses a quantitative approach with data collection through google forms. The data used in this study consisted of 32 indicators and the number of respondents in this study were 320 respondents who were Netflix customers in Jabodetabek. Data analysis uses AMOS-SEM version 24. The results of this study indicate that brand credibility has a positive relationshipwith brand-self connection; brand credibility does not have a positive relationship with brand-social connections; brand-self connection has a positive relationship with brand-social connection; brand-social connections have a positive relationship with word of mouth; brand credibility has a positive relationship with word of mouth mediated by brand-self connection and brand-social connection; brand-social connections have a positive relationship with electronic word of mouth; brand credibility has a positive relationship with electronic word of mouth mediated by brand-self connection and brand-social connection; and brandcredibility has a positive relationship with brand-self connections that are moderated by a brand experience memorial. Key Words: Brand Credibility, WOM, e-WOM, Brand-self Connection, Brand-SocialConnection, Memorial Brand Experience